Identification of Amino Acid Residues Important for Sarpogrelate Binding to the Human 5-Hydroxytryptamine2A Serotonin Receptor - Habib Abul Muntasir; Mamunur Rashid; Tadazumi Komiyama; Jun Kawakami; Takafumi Nagatomo (Elsevier, 2006)
The purpose of the present study was to examine 5-hydroxytryptamine (5-HT)2A-receptor sarpogrelate interactions by site-directed mutagenesis. Based on molecular modeling studies, aspartic acid (Asp)155[3.32] and tryptophan (Trp)151[3.28] in transmembrane helix (TMH) III and Trp336[6.48] in TMH VI of the 5-HT2A receptor were found to interact with sarpogrelate. All of these residues were mutated to alanine (Ala). The Asp3.32Ala mutant did not exhibit any affinity for [3H]ketanserin, whereas the Trp3.28Ala mutant showed a markedly decrease in the binding affinity for [3H]ketanserin (Kd >10,000 nM). Therefore, it was not possible to find any sarpogrelate affinity to the mutants using [3H]ketanserin. The mutation also abolished agonist-stimulated formation of [3H]inositol phosphates (IP) in both cases. On the other hand, the Trp6.48Ala mutant showed reduced binding affinity for [3H]ketanserin (Kd 2.0 nM vs 0.8 nM for the wild-type receptor) and had reduced affinity for sarpogrelate (pKi value of 5.71 vs 9.06 for the wild-type receptor). The Trp6.48Ala mutant also showed the greatest decrease in sensitivity to sarpogrelate (pKb value 8.81 for wild-type and 5.11 for mutant) in inhibiting agonist-stimulated IP formation. These results provide direct evidence that Asp3.32, Trp3.28, and less importantly, Trp6.48 are responsible for the interaction between the 5-HT2A receptor and sarpogrelate. In addition, these results support the findings obtained from molecular modeling studies. Keywords:: 5-hydroxytryptamine (5-HT), 5-HT2A receptor, sarpogrelate, site-directed mutagenesis, molecular modeling